2016
DOI: 10.1007/s12262-015-1438-x
|View full text |Cite
|
Sign up to set email alerts
|

Wound Outcome Following Primary and Delayed Primary Skin Closure Techniques After Laparotomy for Non-Traumatic Ileal Perforation: a Randomized Clinical Trial

Abstract: To study the effect of primary and delayed primary closure of skin incision on wound outcome in patients with non-traumatic ileal perforation, 68 patients of ileal perforation were studied in a prospective randomized clinical trial. Patients fulfilling inclusion criteria were divided into ileostomy and non-ileostomy groups, both of which were then randomized into two subgroups each depending on whether skin was closed primarily or in a delayed primary manner. Wound infection and dehiscence were the main outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…This finding of present study was consistent with reports of other studies. 17 The mortality rate in present study was only 3.8% and is lower than many reports from developing countries where it is reported from 9-22%. Less rates of mortality in present study may be due to improved hospital care, better surgical technique and well developed infra structure.…”
Section: Discussioncontrasting
confidence: 78%
“…This finding of present study was consistent with reports of other studies. 17 The mortality rate in present study was only 3.8% and is lower than many reports from developing countries where it is reported from 9-22%. Less rates of mortality in present study may be due to improved hospital care, better surgical technique and well developed infra structure.…”
Section: Discussioncontrasting
confidence: 78%
“…This is achieved by allowing free egress of wound exudates [3]. However, leaving this wound for 3 to 5 days while waiting for delayed primary closure is usually frightening and causes anxiety in patients and their caregivers [9]. This has been one of the reasons why many surgeons practice primary closure of such wounds [7].…”
Section: Discussionmentioning
confidence: 99%
“…The method of skin closure is an important factor that influences the outcome of a surgical wound [9]. Wound closure after laparotomy for typhoid ileal perforation can either be primary or delayed primary closure [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand delayed primary wound closure prevents the formation of seroma and anaerobic environment in the wound, thus avoiding bacterial proliferation. 23 Another postulate in favour of delayed primary wound closure is that, leaving open the wounds, as in delayed primary wound closure, prevent infection as repeated dressing change accomplishes adequate drainage. 15 Over all incidence of incisional hernia in the present study population was 8.5%, with 7.5% in primary suture group and a slightly higher-9.4% in the delayed primary suture group, though not statistically significant (Table 12).…”
Section: Discussionmentioning
confidence: 99%
“…Similar pattern of organism were seen in a study conducted by Agrawal et al who reported that most common organism isolated from pus culture as Escherichia coli in 35 % followed by mixed growth in 8.8% and Klebsiella 4.4% and Staph aureus, Enterobacter, and Pseudomonas in 1.4% and 7.3%. 23 Jadesh et al who compared primary closure and delayed primary closure demonstrated the most common organism cultured from the wounds as E. coli 13%, Klebsiella 17%, Pseudomonas 21%, Staphylococcus aureus 9%, coagulase negative staphylococci 4%, enterococci 4% and sterile 36%. 28 The method of delayed primary wound closure has the advantage of reducing the numbers of colonic bacteria, particularly anaerobes, contaminating the wound.…”
Section: Discussionmentioning
confidence: 99%